2016
DOI: 10.2185/jrm.2915
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition among children under 5 years of age in Yemen: Role of adequate childcare provided by adults under conditions of food insecurity

Abstract: Objective: This study examined the associations between the adequacy of childcare provided by adult caretakers and childhood undernutrition in rural Yemen, independent of household wealth and food consumption.Methods: We analyzed data of 3,549 children under the age of 5 years living in rural areas of Yemen based on the 2013 Yemen Baseline Survey of Mother and Child Health. Nutritional status was evaluated by the presence of underweight, stunting, and wasting according to the World Health Organization child gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
3
13
2
Order By: Relevance
“…This might be due to the fact that mothers in food insecure areas were at a high risk of getting underweight babies [ 7 ], while participants in this study lived in a food secure area that maximized the frequency of feeding, and making it possible for providing diversified food provision. Similarly, the finding was lower than findings overseas, for example, Bangladesh 43% [ 31 ], Yemen 46.2% [ 17 ], and Nepal 27.4% [ 32 ]. The possible justification for this could be variations among participants in wealth, access to health care, and differences in socio-demographic characteristics [ 17 , 33 ].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This might be due to the fact that mothers in food insecure areas were at a high risk of getting underweight babies [ 7 ], while participants in this study lived in a food secure area that maximized the frequency of feeding, and making it possible for providing diversified food provision. Similarly, the finding was lower than findings overseas, for example, Bangladesh 43% [ 31 ], Yemen 46.2% [ 17 ], and Nepal 27.4% [ 32 ]. The possible justification for this could be variations among participants in wealth, access to health care, and differences in socio-demographic characteristics [ 17 , 33 ].…”
Section: Discussionmentioning
confidence: 63%
“…Lack of dietary diversity and micronutrient-dense food consumption and poor child feeding practices contribute to the high rate of child under nutrition. Various reports also indicate that underweight in children is mainly caused by inadequate food intake [ 7 , 8 ], repeated infections [ 9 – 11 ], low parental education [ 12 14 ], lack of sanitation [ 15 ], poor feeding practices [ 16 ], no ANC [ 17 19 ], residence [ 20 ], child rearing practices [ 21 ], economic [ 21 , 22 ], social, and cultural factors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether antenatal care is being made use of or not has been an important factor on determining the stunting status of children. Literature exhibits the idea that non-use of antenatal care is associated with a prevalence of stunting [45], and children whose mother received antenatal care are less likely to be stunted [46,47]. From this perspective, a key policy suggestion for the government would be expansion of antenatal care services to the far-reaching corners of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Calibration was done before weighing every child by setting it to zero. In the case of children age below two years, the scale was allowed weighing of very young children through an automatic mother-child adjustment that used to eliminate the mother's weight while she standing on the scale with her baby (17).…”
Section: Anthropometric Datamentioning
confidence: 99%
“…Though childhood underweight continues to be the leading public health problem in developing countries, it can occur as a result of a wide range of factors. Various reports have been indicated that underweight in children is mainly caused by inadequate food intake (13,14), repeated infections (15,16), poor feeding practices (16), lack of ANC follow up (17,18), rural residence (19), child-rearing practices (20), low economic status (20,21), social, and cultural factors (22) In Ethiopia, the magnitude of underweight was still high. Evidences claimed that according to the 2016 EDHS report underweight was 41% in 2000, 33% in 2005, and 29% in 2011, and24 in 2016 (23).…”
Section: Introductionmentioning
confidence: 99%